2011
DOI: 10.1002/pmic.201000186
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins secreted by head and neck cancer cell lines using LC‐MS/MS: Strategy for discovery of candidate serological biomarkers

Abstract: In search of blood-based biomarkers that would enhance the ability to diagnose head and neck/oral squamous cell carcinoma (HNOSCC) in early stages or predict its prognosis, we analyzed the HNOSCC secretome (ensemble of proteins secreted and/or shed from the tumor cells) for potential biomarkers using proteomic technologies. LC-MS/MS was used to identify proteins in the conditioned media of four HNOSCC cell lines (SCC4, HSC2, SCC38, and AMOSIII); 140 unique proteins were identified on the basis of 5% global fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 83 publications
2
26
0
Order By: Relevance
“…To filter out likely intracellular contaminants and retain proteins most likely to be secreted by live cells, we used the SignalP [26,27] and Gene Ontology (GO) [28,29] databases to retain only proteins either experimentally observed to be extracellular or otherwise containing predicted cleavable signal peptides targeting them to the secretory pathway. This analysis yielded a total of 298 unique, secretory-predicted proteins across the eight cell lines, which is in line with previous quantities and percentages of secreted proteins found in comparable secretome analyses [8,[30][31][32][33][34][35][36][37][38][39][40].…”
Section: Non-quantitative Bone Metastasis Secretome Analysissupporting
confidence: 57%
See 1 more Smart Citation
“…To filter out likely intracellular contaminants and retain proteins most likely to be secreted by live cells, we used the SignalP [26,27] and Gene Ontology (GO) [28,29] databases to retain only proteins either experimentally observed to be extracellular or otherwise containing predicted cleavable signal peptides targeting them to the secretory pathway. This analysis yielded a total of 298 unique, secretory-predicted proteins across the eight cell lines, which is in line with previous quantities and percentages of secreted proteins found in comparable secretome analyses [8,[30][31][32][33][34][35][36][37][38][39][40].…”
Section: Non-quantitative Bone Metastasis Secretome Analysissupporting
confidence: 57%
“…The first breast cancer metastasis secretome study profiled the secretomes of the MCF10A metastasis progression series, finding proteins such as alpha-1-antichymotrypsin and galectin-3-binding protein to be upregulated in conditioned media from the metastatic variants [48]. More recently, many secretome analyses of cell lines representing several different cancer types have been reported [8,[30][31][32][33][34][35][36][37][38][39][40]. Most secretome studies have used methodology similar to ours in terms of initial protein harvesting conditions and then have typically used either concentrating columns or total protein precipitation methods for secreted protein isolation.…”
Section: Mario Andres Blanco Et Al 1349mentioning
confidence: 99%
“…These are key biological processes occurring at the cell surface or the extracellular vicinity of tumor cells; thus, it serves as no surprise that proteins involved in these diverse processes were identified in this study. Ralhan et al reported the only secretome profiling of a similar HNC subsite, examining the CM of the human laryngeal SCC cell line (SCC38), in addition to oral SCC cell lines, which has resulted in fewer protein identifications, likely because of a different proteomics analysis strategy (53). We further extended our results by systematic validation in wellannotated patient tissue and plasma samples.…”
Section: Discussionmentioning
confidence: 63%
“…Each set was then separated via off-line SCX chromatography using an HP1050 HPLC instrument (Agilent, Palo Alto, CA) with a 2.1-mm internal diameter ϫ 100-mm length PolyLC Polysulfoethyl A column packed with 5-m beads with 300-Å pores (The Nest Group, Southborough, MA) as described elsewhere (27). Separation was performed using a linear binary gradient over 1 h (see details in supplemental Table S3) of Buffer A and Buffer B; Buffer B was composed of Buffer A and 350 mM potassium chloride.…”
Section: Methodsmentioning
confidence: 99%